Analytical investigation on the load-moment characteristics of GFRP bar reinforced circular NSC and HSC columns. (20th September 2018) - Hasan, Hayder Alaa; Sheikh, M. Neaz; Hadi, Muhammad N.S.
Highlights: Procedures of establishing analytical P − M interaction diagrams are proposed. Behaviour of GFRP bar reinforced NSC (GFRP-NSC) columns is investigated. Behaviour of GFRP bar reinforced HSC (GFRP-HSC) columns is investigated. Axial load-bending moment interactions of GFRP-NSC columns are presented. Axial load-bending moment interactions of GFRP-HSC columns are presented. Abstract: In this study, the efficiency of Glass Fibre Reinforced-Polymer (GFRP) bar reinforced normal strength concrete (NSC) and high strength concrete (HSC) columns in sustaining axial and flexural loads was analytically investigated. Experimental data from available literature were used as benchmarks for the analytical investigations conducted in this study. In addition, a comprehensive parametric study was carried out to investigate the effect of different parameters (i.e., compressive strength of concrete, mechanical properties and reinforcement ratio of GFRP bars, and slenderness ratio of the columns) on the performance of concrete columns reinforced with GFRP bars. It was observed that under concentric axial load, the improvements in the axial load carrying capacity due to increasing GFRP longitudinal reinforcement ratio were more pronounced in GFRP bar reinforced NSC columns than in GFRP bar reinforced HSC columns. It was also observed that HSC columns reinforced longitudinally with GFRP bars with small longitudinal reinforcement ratio or low tensile modulus of elasticity might experience a tensile failure of the GFRP bars located on the tension side of the column cross-sections, especially if the columns are subjected to a high level of axial load eccentricity.